High-resolution label-free 3D mapping of extracellular pH of single living cells - Zhang, Yanjun; Takahashi, Yasufumi; Hong, Sung Pil; Liu, Fengjie; Bednarska, Joanna; Goff, Philip S.; Novak, Pavel; Shevchuk, Andrew; Gopal, Sahana; Barozzi, Iros; Magnani, Luca; Sakai, Hideki; et al. (Nature communications, 2019)
Dynamic mapping of extracellular pH (pHe) at the single-cell level is critical for understanding the role of H + in cellular and subcellular processes, with particular importance in cancer. While several pHe sensing techniques have been developed, accessing this information at the single-cell level requires improvement in sensitivity, spatial and temporal resolution. We report on a zwitterionic label-free pH nanoprobe that addresses these long-standing challenges. The probe has a sensitivity > 0.01 units, 2 ms response time, and 50 nm spatial resolution. The platform was integrated into a double-barrel nanoprobe combining pH sensing with feedback-controlled distance dependance via Scanning Ion Conductance Microscopy. This allows for the simultaneous 3D topographical imaging and pHe monitoring of living cancer cells. These classes of nanoprobes were used for real-time high spatiotemporal resolution pHe mapping at the subcellular level and revealed tumour heterogeneity of the peri-cellular environments of melanoma and breast cancer cells. Current methods to measure extracellular pH are often limited in resolution and response times. Here the authors present a label-free nanoprobe, consisting of a zwitterionic nanomembrane at the tip of a nanopipette, which enables high spatiotemporal resolution pH measurements and topography-pH 3D mapping in live cancer cells.